2021
DOI: 10.3390/ma14092169
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Electrical Performance of Flexible Polymer Film Designed for a Textile Electrically-Conductive Path

Abstract: Electro-conductive paths that are mechanically resistant and stable during simulated aging cycles are promising, in relation to the non-invasive application in e-textiles in our everyday surroundings. In the paper, an analysis of the influence of electro-conductive filler, as well as ionic liquid on surface resistance is provided. Authors proved that depending on the tested variant, obtained surface resistance may vary from 50 kΩ (when 50 phr of Ag and [bmim][PF6] ionic liquid applied) to 26 GΩ (when 25 phr of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…After the modification of carbon black with ILs, it was found that the size of the carbon black aggregates became smaller (as shown in the SEM images of Figure 2). Meanwhile, the ILs improved the compatibility between carbon black and silicone rubber (SR), resulting in composites with a lower percolation threshold compared to those of unmodified carbon black [71,80].…”
Section: Carbon Blackmentioning
confidence: 99%
See 1 more Smart Citation
“…After the modification of carbon black with ILs, it was found that the size of the carbon black aggregates became smaller (as shown in the SEM images of Figure 2). Meanwhile, the ILs improved the compatibility between carbon black and silicone rubber (SR), resulting in composites with a lower percolation threshold compared to those of unmodified carbon black [71,80].…”
Section: Carbon Blackmentioning
confidence: 99%
“…lecules 2023, 28, x FOR PEER REVIEW aggregates became smaller (as shown in the SEM images of Figure 2). improved the compatibility between carbon black and silicone rubbe composites with a lower percolation threshold compared to those of black [71,80].…”
Section: Carbon Blackmentioning
confidence: 99%